The symbiotic role of marketing and identity on transitional consumption to the ideal body as facilitated by a fitness-driven lifestyle - Thomas, Gerard (2015)
Globally, the health and fitness trend has been going. This is an industry that is highly image centric. However, there has been little research done on identity in this area, particularly fitness. This study intends to help close this gap by addressing the following topics: consumers’ deep motivations for obtaining the ideal body as facilitated by a fitness-driven lifestyle; whether marketing influences these motivations and how; and whether and how marketing influences consumers’ transition to this ideal body. The findings of this research concur mostly with prior literature. Consumers are motivated to obtain the ideal body in order to adopt social roles, be sexually desirable, and take control of their body. However, this study had the novel finding that consumers also want a better body to be able to wear certain clothes and, therefore, express a fashion-based identity. Marketing influenced these motivations by encouraging those with low self-esteem to pursue a fitness-identity in order to raise it, and encouraged those with high self-esteem in order to be self-consistent. Marketing was also found to have a major impact during the transition period. It facilitated the transition by reducing uncertainty and liminality, helping consumers achieve the ideal self, and helping to bridge identities. However, it also complicated the transition at times by increasing uncertainty and liminality, and facilitating exercise dependence. Further, with respect to liminality, this study had the novel finding that consumers do not necessarily only reintegrate into their former roles or separate into a new role, but they may also separate into the new role and then later revert to the old. These findings were considered to be of academic and practical value, and therefore, future research areas as well as managerial implications were proposed.